If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 + 4p = -8(7p + 3) + -3 Reorder the terms: -27 + 4p = -8(3 + 7p) + -3 -27 + 4p = (3 * -8 + 7p * -8) + -3 -27 + 4p = (-24 + -56p) + -3 Reorder the terms: -27 + 4p = -24 + -3 + -56p Combine like terms: -24 + -3 = -27 -27 + 4p = -27 + -56p Add '27' to each side of the equation. -27 + 27 + 4p = -27 + 27 + -56p Combine like terms: -27 + 27 = 0 0 + 4p = -27 + 27 + -56p 4p = -27 + 27 + -56p Combine like terms: -27 + 27 = 0 4p = 0 + -56p 4p = -56p Solving 4p = -56p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '56p' to each side of the equation. 4p + 56p = -56p + 56p Combine like terms: 4p + 56p = 60p 60p = -56p + 56p Combine like terms: -56p + 56p = 0 60p = 0 Divide each side by '60'. p = 0.0 Simplifying p = 0.0
| 14X+9y=216 | | 6+7y=3y-3 | | -6w-2(-3x+6w)+2x= | | 8x(-7)+8-(-10)= | | 7=-16x^2+24x+1 | | 1.5=10*1 | | 15(-21x+20)=15(-4x+122) | | 2x-3=8x-33 | | 6.2x+6.6-3.4x=20.6 | | 23=3x | | -17=3x-8 | | -5x+46=5+9(8x-4) | | a^3-1698a-2704=0 | | -4x-10=11 | | 1m+10=80 | | 33-x=222 | | 3(9x+7)=27x-1 | | 5(3-2x)=10(4-2x)-85 | | 4(x-10)=5x-45 | | 2x-5x-2=-3+4x-43 | | y=-1+-0.1666666667x | | IV=ir | | a^4-1698a-2704=0 | | 88-6x=-10x+85 | | -46-8x=5(-7x+7) | | 3=5-2 | | 75+10=15h | | 2(1.5)-3y=2 | | 4u-6=-2 | | p-0.30p=25.20 | | -20=4w | | 8x+6x-20=60-6x |